Trigeminal Neuralgia - Impact on Daily Activities and Sports, Treatment Options That Enable a Pain-Free Life - Ewelina Kisiel-Cybula; Irena Sionek-Wręga; Eliza Jakubowska; Julia Ślemp; Anita Pakuła; Krzysztof Kuźma; Karolina Bierć; Marcelina Grochowska; Ewa Hoppe-Mitera; Jakub Wręga (Journal of Education, Health and Sport, 2024)
The review highlights that TN has a prevalence of 0.16%–0.3%, predominantly affecting women, with an increased incidence among individuals over 50 years of age. TN etiology includes neurovascular compression, demyelinating conditions like multiple sclerosis, and familial genetic predispositions. Classification systems, such as the 2018 ICHD-3, provide diagnostic criteria and categorize TN into classical, secondary, and idiopathic types. First-line treatments involve antiepileptic medications such as carbamazepine and oxcarbazepine, with second-line options including lamotrigine and baclofen. For refractory cases, microvascular decompression and percutaneous techniques are recommended, with options like gamma knife radiosurgery (GKRS) and botulinum toxin injections showing promise. Despite available treatments, TN’s recurrent nature underscores the need for personalized, multidisciplinary management to address both physiological and mental health impacts.